НИЙГМИЙН ХҮМҮН БҮТЭЦ ДЭХ ХӨӨРСӨН ТҮМЭН - Даш-Ёндон, Д (Proceedings of the Mongolian Academy of Sciences, 2016)
The article attempts to divide into icons of social human realities and ideal as an abstractive humane structure classified by shapes and regards to explaining the concept that people are lifted within this image. Concerning of author’s reason excited that “demonstrations was conjuncture as individual for “I” consciousness has dissolved, and appealed that elimination of the laws, ethics were effected to roaming people in the appealed to the commission of the offenses.